2023
DOI: 10.3390/ijms24087445
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Post-COVID Syndrome: A Cross-Sectional Study in a Cohort of Italian Workers

Abstract: In addition to the acute symptoms after infection, patients and society are also being challenged by the long-term effects of COVID-19, known as long COVID. Oxidative stress, as a pivotal point in the pathophysiology of COVID-19, could potentially be also involved in the development of the post-COVID syndrome. The aim of the present study was to evaluate the relationship between changes in oxidative status and the persistence of long-COVID symptoms in workers with a previous mild COVID-19 infection. A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
2
13
0
2
Order By: Relevance
“…Our previous report also demonstrated significantly increased oxidative stress and decreased antioxidant markers in patients undergoing HD with long COVID compared to fully recovered patients [ 34 ]. Additionally, in line with our findings, Stufano et al proposed MDAs as an independent predictor of long COVID in Italian workers [ 35 ], and Restea et al demonstrated decreased ceruloplasmin levels in patients with type 2 diabetes and severe COVID-19 [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our previous report also demonstrated significantly increased oxidative stress and decreased antioxidant markers in patients undergoing HD with long COVID compared to fully recovered patients [ 34 ]. Additionally, in line with our findings, Stufano et al proposed MDAs as an independent predictor of long COVID in Italian workers [ 35 ], and Restea et al demonstrated decreased ceruloplasmin levels in patients with type 2 diabetes and severe COVID-19 [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The more convincing explanation at present is that pulmonary neovascularization plays a beneficial effect in abnormal lung recovery in some patients [ 31 , 47 ]. Recent studies have reported a potential role for peripheral circulating redox imbalance in the pathogenesis of long COVID, yet the relationship between pulmonary redox imbalance and long-term lung abnormalities in COVID-19 survivors has rarely been reported [ 65 , 66 ]. A common sequela of COVID-19 is pulmonary fibrosis [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled a cohort of workers from the University of Bari (Apulia, Italy), who requested to be assessed by the University Occupational Health Unit physicians, following an asymptomatic SARS-CoV-2 infection or a mild COVID-19 diagnosed by molecular test (COVID-19 patients), according to the internal procedure for returning to work. The calculation of the minimum sample size was performed a priori considering the prevalence of long COVID in a previous study in a similar population 20 and taking into account the results of the Global Burden of Disease analysis 21 accepting a 2% margin of error and a 95% confidence interval. Mild COVID-19 individuals were those who presented any of the several signs and symptoms of COVID-19 (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Mild COVID-19 individuals were those who presented any of the several signs and symptoms of COVID-19 (e.g. fever, sore throat, cough, malaise, migraine, muscular pain, vomiting, nausea, diarrhea, and loss of taste and smell), but without shortness of breath, dyspnoea or abnormal chest images 20 . Asymptomatic infected individuals were those with a positive SARS-CoV-2 virological test but without symptoms consistent with COVID-19 22 .…”
Section: Methodsmentioning
confidence: 99%